MRSA screening and spa gene detection in isolates from healthcare workers at ophthalmology hospital in Egypt - Haggag, Maha G. (2021)
In the present study, 81 samples from healthcare providers in the hospital of the Research Institute of Ophthalmology, Egypt, were screened for MRSA. Out of these 81 samples, 41 isolates (50.6%) were identified as coagulase-positive Staphylococcus aureus. Twelve staphylococcal isolates were resistant to both oxacillin and cefoxitin, and those were identified as MRSA with a percentage of 14.8% (12/81). Conventional PCR could detect spa gene in 10 out of 12 DNA MRSA with a percentage of 83.3% (10/12).